Peran Perempuan Sebagai Buruh Pasir dalam Meningkatkan Kesejahteraan Ekonomi Keluarga Studi Kasus di Dusun Butus Desa Bhuana Giri - Ni Kadek Mita Handayani; Luh Indrayani (Ekuitas: Jurnal Pendidikan Ekonomi, 2025)
Village, choose to work as sand laborers even though they have to play a dual role as housewives and breadwinners, and to describe the contribution of this work to the economic welfare of their families. This study uses a qualitative approach with a case study method and involves 10 key informants. Data were collected through observation, in-depth interviews, and documentation, then analyzed using the help of Nvivo 12 Pro software through the stages of data import, coding, visualization, and reporting. The results of the study indicate that economic coercion and limited job choices encourage women to work as sand laborers. Although this work is physically difficult, they still do it as a form of responsibility towards their families. This activity contributes to the fulfillment of basic needs, children's education, and household economic stability. The novelty of this study lies in the local context of women in the sand mining sector with high domestic role pressures.